Tinjauan Yuridis Sengketa Tanah Akibat Perbuatan Melawan Hukum: Studi Kasus Putusan No.88/Pdt.G/2020/PN.Bks - Joko Priambodo; Ardhira Iskandar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
One example of an unlawful act is illegally occupying land and buildings without the owner's permission, which gives rise to disputes. Land conflict (dispute) is an action aimed at obtaining legal protection provided by the court to prevent acts of self-judgment (eigenrichting). The development of land conflicts/disputes, both in quality and quantity, is always increasing, while the main factor in the emergence of land conflicts is the fixed area of ​​land, while the number of people who need land (humans) to meet their needs is always increasing. So, in land disputes, if the parties do not want to resolve the case peacefully, they can resolve it by submitting the case to the District Court. However, in practice, in a case the losing party does not want to accept the court's decision and then files an appeal, cassation and judicial review. In this research, the author uses a normative research method, namely research by analyzing applicable legal norms, both in the form of laws and court decisions. Research data was obtained from library materials and primary legal documentation, namely Law no. 5 of 1960 concerning the Basic Agrarian Law, Government Regulation no. 24 of 1997 concerning Land Registration, secondary and tertiary legal materials. The results of this research show that land disputes in Indonesia are resolved in the usual way through the General Court and State Administrative Court with incomplete and suboptimal results. This is caused by overlapping decisions that have been determined by each judicial body, the difficulty of executing decisions of judicial bodies that have permanent legal force and the lack of clarity regarding which laws and regulations are competent to resolve land cases in Indonesia. There are six roots of land conflict in particular, namely first, the issue of disputes over court decisions. Second, the issue of land rights applications related to forest area claims. Third, the issue of boundary disputes and land registration as well as overlapping certificates on the same land. Fourth, the problem of reclaiming and reoccupying land that has been released by housing developers due to manipulated compensation. Fifth, land issues regarding ulayat or customary land claims. Sixth, problems related to plantation land.